Autologous platelet-rich plasma application for the optimization of bone tissue reparative regeneration in osteopenia - D. V. Ivchenko; V. V. Miroshnikov (Zaporozhye State Medical University, 2018)
Objective: analysis of scientific literature on the effectiveness of using Plateled-Rich Plasma to optimize the treatment of compression fractures of vertebral bodies of thoracic and lumbar localization against the background of postmenopausal and senile osteoporosis. All the methods of using Platelet-Rich Plasma, described in the literature, can be divided into several main groups. Platelet-Rich Plasma can be mixed with bone material; is applied to the lesion site before application of bone material; is applied over the bone material; used as a biological membrane. Platelet-Rich Plasma contain fibrillar and cellular components and is able to act as a carrier of cells which are important for the regeneration of soft and bony tissues. It can strengthen the attachment of human osteoblasts to membranes and, as a consequence, induce osteogenesis. Many authors are the supporters of the stimulating effect of Platelet-Rich Plasma on reparative osteogenesis. After injection of Platelet-Rich Plasma in the case of complicated fracture the following was observed: odema in the damaged tissues is less pronounced, there are less signs of acute and chronic inflammation, the phase of alteration is changing more quickly by regenerative-reparative processes. The natural clot contains fibrin, fibronectin and vitronectin, they are also called adhesion molecules necessary for cell migration, osteoconduction, epithelialization and osseointegration. Biological properties of Platelet-Rich Plasma are due not only to the presence of growth factors (TGF-β and PDGF), but without them it immediately induces the formation of a fibrin clot, followed by stimulation of cell adhesion and collagen synthesis. Conclusion. Based on the published literature, a high potential of plasma therapy by Platelet-Rich Plasma for bone tissue regeneration is demonstrated. No adequate clinical studies on the effectiveness of Platelet-Rich Plasma therapy that would meet all modern criteria have yet been conducted. Therapy of Platelet-Rich Plasma is a promising branch in medicine and deserves further research in terms of new effective and safe method of application in medical practice.